1973
DOI: 10.1111/j.1476-5381.1973.tb08224.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E1 causes sedation and increases 5‐hydroxytryptamine turnover in rat brain

Abstract: Summary1. Administration of prostaglandin E1 (1 mg/kg, i.p.) to rats induced sedation and a decrease in muscular tone. Prostaglandin El-induced sedation was accompanied by the low voltage-high frequency E.E.G. pattern characteristic of the waking animal. 2. Administration of prostaglandin E1 also increased the turnover rate of 5-hydroxytryptamine and raised the concentration of acetylcholine in brain. 3. The behavioural effects of prostaglandin were blocked by prior administration of p-chlorophenylalanine or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In addition, Bhattacharya & Sanyal(1978) reported that the threshold for leptazol seizure was reduced by prostaglandin El, Correspondence. which increases the 5-HT turnover and elevates the steady state concentrations of its neutral metabolites in the brain (Haubrich et al 1973;Fukumori et al 1980b).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Bhattacharya & Sanyal(1978) reported that the threshold for leptazol seizure was reduced by prostaglandin El, Correspondence. which increases the 5-HT turnover and elevates the steady state concentrations of its neutral metabolites in the brain (Haubrich et al 1973;Fukumori et al 1980b).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Bhattachrya and Sanyal (24) demonstrated that the incidence of seizures after PTZ adminis tration was significantly reduced by pro staglandin E, which enhances 5-HT turnover (25,26). Kilian and Frey (9) suggested that although 5-HT played a role mediating both clonic and tonic components of PTZ seizures, it might be more crucially involved in the latter.…”
Section: Discussionmentioning
confidence: 99%
“…2), a highly selective EP 4 receptor agonist, and PF-04475270 (5), a novel ocular hypotensive compound. In order to develop medicinally relevant analogues, we embarked on the enantioselective synthesis of 8-aza-PGE 1 (7) and the 11-hydroxylated analogues (8 and 9) of the leads CP-734432 (4) and PF-04475270 (5) in light of the structure, medical usage [10] and side effects [11] of PGE 1 (alprostadil, 6).…”
Section: Introductionmentioning
confidence: 99%